Bengal ryots, their rights and liabilities : being an elementary treatise on the law of landlord and tenant - Caṭṭopādhyāẏa, Sañjībacandra, 1834-1889 (K. P. Bagchi, 1977)
History of the land tenure system in Bengal during the 19th century.